Bilibili’s stock trajectory: Insights and strategies for digital platforms - Sun Kecheng; Wu Zixuan (SHS Web of Conferences)
This study delves into the stock performance of Bilibili, a vibrant online platform launched on June 26, 2009, that has captivated the youth in China. By examining a multitude of factors such as market trends, competitive dynamics, industry outlook, macroeconomic influences, user demographics, content diversity, creator engagement, commercialization strategies, and international expansion efforts, the research forecasts Bilibili’s trajectory in the stock market. It also scrutinizes the company’s operational paradigm, bolstered by insights from a comprehensive questionnaire that underscores the psychological appeal and operational tactics that draw users to the platform. These tactics include strategic repositioning, effective communication of information, leveraging big data for targeted content delivery, understanding consumer and creator motivations, fostering a rich content creation environment, and employing precision marketing techniques. The paper concludes with strategic recommendations derived from the analysis, aimed at enhancing the platform’s market presence and stock performance. The findings offer invaluable insights for other platforms seeking to emulate Bilibili’s success.